DELTA2 guidance on choosing the target difference and undertaking and reporting the sample size calculation for a randomised controlled trial - Cook, J; Julious, SA; Sones, WR; Hampson, LV; Hewitt, C; Berlin, JA; Ashby, D; Emsley, R; Fergusson, DA; Walters, SJ; Wilson, ECF; Maclennan, G; et al. (BioMed Central, 2018)
Background This article on choosing the target difference for a randomised controlled trial (RCT) and undertaking and reporting the sample size calculation has been dual published in the BMJ and BMC Trials journals. A key step in the design of a RCT is the estimation of the number of participants needed in the study. The most common approach is to specify a target difference between the treatments for the primary outcome and then calculate the required sample size. The sample size is chosen to ensure that the trial will have a high probability (adequate statistical power) of detecting a target difference between the treatments should one exist. The sample size has many implications for the conduct and interpretation of the study. Despite the critical role that the target difference has in the design of a RCT, the way in which it is determined has received little attention. In this article, we summarise the key considerations and messages from new guidance for researchers and funders on specifying the target difference, and undertaking and reporting a RCT sample size calculation. Methods The DELTA2 (Difference ELicitation in TriAls) project comprised five major components: systematic literature reviews of recent methodological developments (stage 1) and existing funder guidance (stage 2); a Delphi study (stage 3); a two-day consensus meeting bringing together researchers, funders and patient representatives (stage 4); and the preparation and dissemination of a guidance document (stage 5). Results and Discussion The key messages from the DELTA2 guidance on specifying the target difference are presented. Recommendations for specifying the target difference and the subsequent reporting of the sample size calculation are provided.